Kinetic thermal degradation of vitamin C during microwave drying of okra and spinach - Dadali, Goekce; Ozbek, Belma (TAYLOR & FRANCIS LTD, 2009)
In this present study, the effect of microwave output power and sample amount on vitamin C loss in okra (Hibiscus esculenta L.) and spinach (Spinacia oleracea L.) were investigated using the microwave drying technique. The procedure is based on the reaction between l-ascorbic acid (vitamin C) and 2,6-dichloroindophenol. The proposed method was applied successfully to both okra and spinach for the determination of ascorbic acid (vitamin C) content. It was observed that as the microwave output power increased or as the sample amount decreased, the vitamin C in okra and spinach decreased as well. The activation energy for degradation of vitamin C for both okra and spinach was calculated using an exponential expression based on the Arrhenius equation.
Keywords: L-Ascorbic acid; kinetic; okra; spinach; microwave drying; ASCORBIC-ACID; STORAGE; MODEL; Food Science & Technology; Nutrition & Dietetics